CONTINUOUS PROFESSIONAL DEVELOPMENT BASED ON INTERNAL COACHING IN SCHOOL INSTITUTIONS - Hikmawati Risa; Nurjannah , Nurjannah; Utomo, Erry (Educational Studies: Conference Series, 2023)
Continuous professional development is a program carried out to improve teacher competence in carrying out their duties. The fact shows that implementing continuous professional development has not significantly improved teacher professionalism. This program has not been running consistently, due to a lack of internal motivation from teachers who tend not to play an active role in the culture of independent learning, because they still position themselves waiting for professional development activities from external parties to improve their competence. This study aims to develop a model of continuous professional development through school institutions based on internal coaching. Internal coaching is the basic capital for teachers to become lifelong learners and self-directed for increasing competency. The research was conducted through a development method using the Smith and Ragan model implemented in an integrated Islamic elementary school that has implemented continuous professional development programs for almost two years, since 2019. The constructed hypothetical model is a continuous professional development model based on internal coaching through the stimulation of reflective, participatory, innovative, and collaborative abilities integrated into the school system to form a culture of independent learning for teachers. The implication of research for further development of teacher empowerment at the school level.